2001
DOI: 10.1007/s002130100899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transdermal nicotine on attention and memory in healthy elderly non-smokers

Abstract: These results suggest that nicotine of lower plasma level can improve short-term verbal memory functions in non-smoking or nicotine-naïve healthy elderly people and that some effects are dependent on nicotine plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 2 publications
2
34
0
1
Order By: Relevance
“…Both drugs reversed scopolamine-induced impairment of serial learning (Sitaram et al, 1978). Within a healthy, nonsmoking sample, nicotine has improved short-term verbal memory functions (Min et al, 2001).…”
Section: Cholinergic Agonistsmentioning
confidence: 94%
See 1 more Smart Citation
“…Both drugs reversed scopolamine-induced impairment of serial learning (Sitaram et al, 1978). Within a healthy, nonsmoking sample, nicotine has improved short-term verbal memory functions (Min et al, 2001).…”
Section: Cholinergic Agonistsmentioning
confidence: 94%
“…Other studies showed that nicotine improved attention and memory in patients with AD or Parkinson's disease (Min et al, 2001;Vidal, 1996). In studies with healthy volunteers, cholinergic enhancers (for example, arecoline, a muscarinic agonist, and choline, a precursor of acetylcholine) have been tested for effects on memory performance after administration of the cholinergic antagonist methscopolamine.…”
Section: Cholinergic Agonistsmentioning
confidence: 96%
“…Possibly, also the decline of memory functions observed during normal aging (Light, 1991;Spencer and Raz, 1995;NavehBenjamin, 2000;Kukolja et al, 2009) is based on a beginning cholinergic deficit (Bartus et al, 1982;Mesulam, 1996;Cohen et al, 2006;Schliebs and Arendt, 2006). Supporting this notion, nicotinic stimulation has been shown to enhance memory performance in healthy elderly adults in several tasks including verbal and object learning, delayed recall, and word retrieval (Howe and Price, 2001;Min et al, 2001). Since nicotine was applied chronically in these studies, the effects on encoding and retrieval were not distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of nicotine to abstinent smokers improves general alertness, attention, and vigilance [4,5]. Nicotine improves performance on vigilance tasks [6,7], inhibition of prepotent responses [8], and verbal learning [9] in nonsmokers. Effects such as these, however, are thought to reflect an influence on general alertness, rather than the primary influence of specific cognitive domains [10,11].…”
Section: Introductionmentioning
confidence: 99%